DISIPLIN KERJA DAN KERJASAMA TERHADAP KINERJA KARYAWAN RUMAH SAKIT: STUDI PADA RUMAH SAKIT UMUM DAERAH GUNUNGKIDUL YOGYAKARTA - Kuncorowati, Heru; Wahyujatmiko, R. Suprono; Supardin, Lalu; Saputri, Lilien Oktatibi (ITB AAS Indonesia Surakarta, 2024)
Hospitals have characteristics as complex service organizations, managing high risks and operating in a dynamic regulatory environment. Staff discipline and teamwork are needed to manage complex work, reduce work error rates, improve work safety and work quality. This study aims to determine and analyze the effect of work discipline and teamwork on employee performance at Wonosari Gunungkidul Yogyakarta Regional Hospital. The study was conducted through a survey using a questionnaire to 100 respondents who were hospital employees. The analysis in this study used multiple linear analysis. The results of the study found the effect of work discipline and cooperation on employee performance at Wonosari Gunungkidul Yogyakarta Regional Hospital.. Keywords : Work Discipline, Teamwork, Employee Performance, Hospital